Estimation of surface layer scaling parameters using SODAR for the coastal site of Tarapur - Vedesh Krishnacharya Varakhedkar (Wolters Kluwer Medknow Publications, 2021)
This report presents the directional dependence of surface scaling parameters, namely, roughness length and corresponding friction velocity, for neutral category at the Tarapur coastal site. The average roughness length of the lowest value of 0.5 m in the west (W) direction and the highest value of 0.885 m in the N direction has been observed and average friction velocity of the lowest value 0.39 m/s in the W direction and the highest value 0.73 m/s in the NW direction was observed for 2019. Sector average turbulent kinetic energy was estimated to be 1.413 m2/s2 and its dissipation rate as 0.33 m2/s3 for the 10 m elevation from the surface. Surface drag coefficient for the 10 m height was 0.0229 for the smooth ocean surface and 0.0255 for the land surface was observed for the Tarapur coastal site.